Apports et perspectives de l’architecture émotionnelle aux sciences et architecture de paysage - Nicolas Gilsoul (Projets de Paysage)
Luis Barragan used the emotional architecture as a new media to inspire human bean in a banalised modern society. His dream feed a specific conceptual procès, based on a scenographic thought (atmosphère settings, spatial script, time évolution). This process follows an universal concept : offer to the human bean what the nasride sultans named in the Alhambra an « inspiring retreat », and what Gilles Clément called today an « interior viewpoint ». This research made by Nicolas Gilsoul in the LAREP – on the conception and perception of this a emotional architecture from Barragan – obtain in june 2009 a doctorat in Sciences and Landscape Design. What are the possible contributions for the research laboratories but also for the designer’s world in landscape projects ?